2022
DOI: 10.3389/fcimb.2022.905841
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Gut Microbiome in Autism and Preclinical Models: A Systematic Review

Abstract: Many individuals diagnosed with autism spectrum disorder (ASD) experience gastrointestinal (GI) dysfunction and show microbial dysbiosis. Variation in gut microbial populations is associated with increased risk for GI symptoms such as chronic constipation and diarrhoea, which decrease quality of life. Several preclinical models of autism also demonstrate microbial dysbiosis. Given that much pre-clinical research is conducted in mouse models, it is important to understand the similarities and differences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 85 publications
3
10
0
Order By: Relevance
“…Since animal models are widely used for studying and understanding psychiatric disorders in humans, it is also important to point out that some genera with increased abundance in individuals with ASD, specifically, Bilophila , Clostridium , Dorea , and Lactobacillus , revealed the same changes in mouse models of autism. Other genera with decreased abundance in autistic individuals, e.g., Blautia , show the same picture in animals, as reported in a recent review [ 112 ]. Many other differences in gut microbiota were found exclusively in humans (e.g., Alistipes , Ruminococcus ) or exclusively in animal models (e.g., Asaccharobacter ) [ 112 ].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Since animal models are widely used for studying and understanding psychiatric disorders in humans, it is also important to point out that some genera with increased abundance in individuals with ASD, specifically, Bilophila , Clostridium , Dorea , and Lactobacillus , revealed the same changes in mouse models of autism. Other genera with decreased abundance in autistic individuals, e.g., Blautia , show the same picture in animals, as reported in a recent review [ 112 ]. Many other differences in gut microbiota were found exclusively in humans (e.g., Alistipes , Ruminococcus ) or exclusively in animal models (e.g., Asaccharobacter ) [ 112 ].…”
Section: Discussionsupporting
confidence: 81%
“…Other genera with decreased abundance in autistic individuals, e.g., Blautia , show the same picture in animals, as reported in a recent review [ 112 ]. Many other differences in gut microbiota were found exclusively in humans (e.g., Alistipes , Ruminococcus ) or exclusively in animal models (e.g., Asaccharobacter ) [ 112 ].…”
Section: Discussionsupporting
confidence: 81%
“…BTBR mice also exhibit dysregulation of both the innate and adaptive systems and an inflammatory immune profile resembling ASD ( Onore et al, 2013 ). Moreover, BTBR mice have prolonged intestinal transit, intestinal barrier dysfunction, and microbial dysbiosis symptoms similar to those reported in patients with ASD ( Leo et al, 2021 ; Alamoudi et al, 2022 ).…”
Section: Introductionsupporting
confidence: 74%
“…In addition, symbionts inhabiting the polysaccharide-rich mucus gel layer overlaying the gut epithelium build a biofilm-like community of microbes that benefit the host by boosting immune responses and digestion of luminal contents (Sonnenburg et al 2004 ). Given that multiple studies in human subjects have shown microbial dysbiosis in neurodevelopmental disorders (reviewed in (Alamoudi et al 2022 )), changes in GALT function and the mucus biofilm environment may be relevant to disruptions in homeostatic mechanisms and the immune response in gut observed in autism.…”
Section: The Role Of Microbes In Peyer’s and Caecal Patch Functionmentioning
confidence: 99%